ANALYSIS OF IMPLEMENTING CHARACTERS OF ENVIRONMENTAL CARE, SOCIAL CARE, AND RESPONSIBILITY EARLY CHILDREN IN TK NEGERI MODEL MADANI PALU - Sudarsana, Wayan; Nadi, Ni Putu Sri; Adnyana, Made Sudimerta (STAH Dharma Sentana Sulawesi Tengah, 2025)
This research aims to analyze the cultivation of caring for the environment, social care, and responsibility in the civil model state kindergarten in Palu. The type of research used is descriptive qualitative by conducting observations, interviews, and documentation. The research results show that teachers implement the values ​​of social care and responsibility by connecting attitudes to learning material. The strategy for implementing social care and responsibility in thematic learning is familiarization through discussion activities, question and answer, role-playing, direct practice, through motivation, messages, or warnings. The social caring attitude that has emerged is having a sense of empathy, and building class harmony, while the attitude of responsibility includes, being serious in everything, trying to do the best, being willing to make sacrifices, being disciplined, trustworthy, obeying orders, honest in actions. and dare to take risks. Supporting factors include student awareness, teacher awareness, school culture, and social activity facilities. Inhibiting factors include student awareness, teacher awareness, and a less supportive family environment.